Hybrid generic algorithm solving flexible process Job-Shop scheduling problem - Ma, Xue-Li; Cao, De-Bi; Liu, Xiao-Bing (Ji suan ji ying yong yan jiu, 2014)
To deal with the problem that many products in discrete manufacturing factories had flexible process design which had increased the complexity of scheduling, this paper proposed the FPJSP as an extension of JSP, and built the mathematical model for the new scheduling problem to shorten the production cycle. It proposed the hybrid genetic algorithm (HGA) to solve the model. According to the characteristics of FPJSP, it designed the genetic algorithm (GA) with improved chromosome encoding schema and genetic operators. In combination with the variable neighborhood search algorithm (VNS), it designed four neighborhood structures to enable dynamic neighborhood search and improve the neighborhood search performance of GA. The experiment shows the effectiveness and optimize performance of the proposed HGA for solving FPJSP.